Analyzing the interest rate risk of banks using time series of accounting-based data: evidence from Germany - Marco Wilkens; Christoph Memmel; Oliver Entrop; Alexander Zeisler (Deutsche Bundesbank, 2008)
This paper describes the first thorough analysis of the interest risk of German banks on an individual bank level. We develop a new method that is based on time series of accountingbased data to quantify the interest risk of banks and apply it to analyze the German banking system. We find evidence that our model yields a significantly better fit of banks' internally quantified interest rate risk than a standard approach that relies on one-point-in-time data, and that the interest rate risk differs between banks of different size and banking group. Additionally, we find structural differences between trading book and non-trading book institutions.
Keywords: G18; G21; 330; German financial institutions; interest rate risk; accounting-based approach; maturity transformation; banking supervision; model evaluation; Bankrisiko; Zinsrisiko; Bilanzanalyse; Bankensystem; Deutschland